Tetrazolium test to estimate the physiological quality of tamarind (Tamarindus indica L.) seeds - Hernández, Jenry Rafael; Iguaran-Diaz, Camilo José; Araméndiz-Tatis, Hermes; Cardona-Ayala, Carlos Enrique; Espitia-Camacho, Miguel Mariano (Revista de Ciencias Agrícolas, 2023)
Tamarind (Tamarindus indica) is a fruit tree of African origin cultivated in more than 50 countries, including Colombia, mainly in the Colombian Caribbean departments, where its harvest generates significant income in rural communities. Its establishment presents a difficulty because the sexual seed presents physical dormancy and poor germination. The objective of this study was to evaluate Tamarind seed viability by using the tetrazolium test and to reduce the time needed for the determination of its physiological quality. Ripe and healthy fruits were collected from patio trees, from which their seeds were extracted, disinfected with 1% sodium hypochlorite, and washed with plenty of water before use. Subsequently, they were scarified with No. 100 sandpaper by the edges, except in the area of the micropyle. The completely random design was used in a 3x3 bifactorial arrangement, with four repetitions. Thefirst factor, tetrazolium concentration (%), was tested at levels of 0.50, 0.75and 1.00%, and the second factor, immersion time, at 2, 4, and 6 hours. The analysis of variance did not show significance for the tetrazolium concentration, while it did for the immersion time(p≤0.01), and the tetrazolium-time interaction(p≤0.05). Therefore, the concentration of 0.50% tetrazolium for six hours of immersion is a reliable alternative to determine the physiological quality of tamarind seeds compared to conventional germination testing due to its low cost and execution time.Likewise, the percentages of germinationand germination speed index were higher when the seed was scarified with sandpaper than the conventional method.